First time reporting of Key Audit Matters (KAM) by Malaysian auditors - Ismail, Hashanah; Abdullah, Asna Atqa; Hassan, Hamimah (Science Publishing Corporation, 2018)
This paper reports on the early first cohort of Audit Reports issued by external auditors in response to the requirement of ISA 701, Communication of Key Audit Matters (KAM) in the Auditor’s Report, which became effective for audits of financial statements on or after 15 December 2016. Based on 15 Audit Reports of financial statements for year ending 31 December 2016 available in early 2017, this paper reports that only one out of 15 had a disclaimer and no KAM reported for the audit as ISA 701 specifies that no KAM should be reported following a disclaimer. The other fourteen audit reports were all clean reports with the number of KAMs reported ranging from one to five. The highest most significant audit matter reported was revenue recognition and inventory valuation followed by asset impairments of both tangible and intangible assets. Justifications by auditors of matters considered most significant ranged from no additional information (it is most significant because it is material) to articulate explicit link with business model and industry specific factors thus compliance with disclosure of KAM may be compliance de jour rather than compliance de facto. Despite the additional requirement to disclose KAM, this study finds no evidence of audit delays. All KAMs disclosed are elaborations of and related to a client’s significant accounting policies choice. From KAM disclosures, readers of audit reports now are informed of the audit risk areas where estimates were made and judgments prevailed challenging auditors to exercise greater skepticism. This preliminary finding provides pointers for greater research into the cost benefits and communicative value of KAM disclosure in the Audit Reports of Listed companies in Malaysia.